Regional meeting on integrated ecological research and training needs in the Sahelian region - Regional Meeting on Integrated Ecological Research and Training Needs in the Sahelian Region, (1(74 Niamey); Programme on Man and the Biosphere (Paris : Unesco, 1975)
01